Effect of the environmental conditions on different morphological and agronomical characteristics of sainfoin - Delgado I.; Andrés C.; Muñoz F. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Morphological and agronomical characteristics of 45 Spanish sainfoin (Onobrychis viciifolia Scop.) entries grown at 3 locations of different altitude under irrigated or non-irrigated conditions in the NE of Spain were compared. Height, number and diameter of stems per plant, number and dimensions of leaflets per leaf, number of inflorescences per plant and forage production as well as flowering evolution in springtime were evaluate on individual plants. Most morphological and productive parameters of plants were reduced when grown in rainfed compared to irrigated areas. Dry matter yield per plant ranged from 153.7 g in rainfed to 557.2 g in irrigated land, similarly distributed in a 67, 21 and 11% for the first three cuts. Flowering and cutting dates seem to be affected by altitude.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)